Beyond Behavior: Linguistic Evidence of Cultural Variation in Parental Ethnotheories of Children’s Prosocial Helping - Coppens, Andrew D.; Corwin, Anna I.; Alcalá, Lucía (Frontiers in Psychology, 2020)
This study examined linguistic patterns in mothers’ reports about their toddlers’ involvement in everyday household work, as a way to understand the parental ethnotheories that may guide children’s prosocial helping and development. Mothers from two cultural groups – US Mexican-heritage families with backgrounds in indigenous American communities and middle-class European American families – were interviewed regarding how their 2- to 3-year-old toddler gets involved in help with everyday household work. The study’s analytic focus was mothers’ responses to interview questions asking about the child’s efforts to help with a variety of everyday household work tasks. Results showed that mothers responded with linguistic patterns that were indicative of ethnotheoretical assumptions regarding children’s agency and children’s prosocial intentions, with notable contrasts between the two cultural groups. Nearly all US Mexican-heritage mothers reported children’s contributions and participation using linguistic forms that centered children’s agency and prosocial initiative, which corresponds with extensive evidence suggesting the centrality of both children’s autonomy and supportive prosocial expectations in how children’s helpfulness is supported in this and similar cultural communities. By contrast, middle-class European American mothers frequently responded to questions about their child’s efforts to help with linguistic forms that “pivoted” to either the mother as the focal agent in the child’s prosocial engagement or to reframing the child’s involvement to emphasize non-help activities. Correspondence between cultural differences in the linguistic findings and existing literature on socialization of children’s prosocial helping is discussed. Also discussed is the analytic approach of the study, uncommon in developmental psychology research, and the significance of the linguistic findings for understanding parental ethnotheories in each community.